ROLE AMBIGUITY AND PSYCHOLOGICAL EMPOWERMENT MEDIATE PERFORMANCE MEASUREMENT SYSTEMS TO MANAGERIAL PERFORMANCE - Prastuti, Rosinta Ery; Yuswanto, Yuswanto (Jurnal Aplikasi Manajemen, 2018)
The purpose of this study is to analyze the effect of Performance Measurement System to Managerial Performance with mediation variables Role Ambiguity and Psychological Empowerment. This type of research is causality. This research was conducted on non-profit organization that is 7 Private University in Malang. The sample in this study the educational staffequivalent to the manager, the number of samples in this study was 79. The data analysis method used in this study is SEM PLS using WarpPLS 5.0 software. The results of this study indicate that the Performance Measurement System has a positive effect on Managerial Performance through mediation variables Role Ambiguity and Psychological Empowerment. Performance Measurement System has a positive and significant effect on managerial performance. The Performance Measurement System has an indirect relationship with Managerial Performance through Psychological Empowerment. The conclusion is that this study supports the hypothesis developed by Marginson, et al. (2015), but there are some unsupported hypotheses because of the different research objects that each type of organization has different characteristics.